FCKAN: Evaluating KAN for Time Series Classification and Extrinsic Regression - Merlin, Gabriel da Costa; Medronha, Adilson Junior Alves; Silva, Diego Furtado (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
Time Series Classification (TSC) and Time Series Extrinsic Regression (TSER) are critical tasks across diverse fields. While Fully Convolutional Networks (FCNs) effectively capture temporal dependencies, Kolmogorov–Arnold Networks (KANs) offer greater flexibility and interpretability. However, integrating KANs with temporal encoders and their application to regression tasks remain largely unexplored. This paper introduces FCKAN and Hybrid FCN-KAN, two novel architectures that combine FCNs and KANs for TSC and TSER. The first is an end-to-end model, while the second is a hybrid approach that leverages a pre-trained FCN as a feature extractor followed by a KAN. We conduct experiments on 147 benchmark datasets. For TSC, both architectures outperform non-temporal baselines and achieve competitive performance with FCNs. In TSER, although all models are statistically equivalent, temporal models consistently outperform non-temporal baselines.